(3OjhGf GdLYHQjs - (3GdLYHQj, EHQGgje Hf eYVGO Hf TOGO, J(B687(3g`s
(3ChdgG (B:s
(3CgOi dbdHj ef dWGFa HQg (B*** (3aTai aDGOj ef MdGhI PcQg , aWQHJ ef fZeGJ WjH MOjKg (B*** (3hScQJ ef UGaj SdGaI NeQgs
(3BNQgG (B:s
(3haj GdTYQ GdePchQ fU PcQgG (B*** (3MdG PcQgG aj eSeYj haj NGWQj , YQHJ GdYde JLQHI Gdbde Ydi GdbQWGS, dG CadM ef Xde GdfGSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 74s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdCOHs